Geotechnical behavior of a tropical residual soil contaminated with gasoline (2015)
The infrastructure for hydrocarbon transportation has grown significantly to supply the needs of a greater number of settlements; however, due to problems in the supply networks, accidental spills or leaks can contaminate the underlying soils. This paper addresses soils contaminated with gasoline, and it analyzes the changes that occur in a tropical residual soil after contamination. Analysis was carried out by using specific laboratory tests to characterize the type of soil (Miniature Compacted Tropical Classification, Suction, Pinhole Test, Collapse Potential, X-ray Diffraction, Scanning Electron Microscopy, pH determination) and by performing traditional tests (natural humidity, specific gravity, granulometry, Atterberg limits, direct shear, etc.). These tests were conducted with samples in their natural state, as well as contaminated samples, in order to elucidate possible variations in the mechanical characteristics of the material.